Executive Committee Minutes 2018-11-15 - Academic Senate:::::::::
Agenda approved with added item. Minutes of 11/1/18 approved. Chair Report. President Report. Provost Report. ASCSU Tenets of System Level Shared Governance document added to Senate Agenda. Discussion about the Emeritus Dinner – referral from the Senate. Statewide Senator Report. Vice Chair Report. APARC Report. EPC Report. FSAC Report. SAC Report. Senate agenda approved. CFA Report. Associated Students Report. SEC Report.